Language, Immigration and Labor : Negotiating Work in the U.S.-Mexico Borderlands - DuBord, Elise M., 1975- (Language and globalization., 2014)
"Language, Immigration, and Labor explores dominant ideologies about citizenship, nation, and language that frame the everyday lives of Spanish-speaking immigrants in the U.S.-Mexico border region. Focussing its ethnographic research on Arizona, a state that intensely regulates transnational migrants and Spanish speakers through its immigration and language policies, this book examines the realities of intercultural communication in fast-paced job negotiations between undocumented workers and their employers. The research reveals the ways that dominant discourses reverberate down to localized social and language practices and how day laborers respond by legitimating their participation in society--a kind of cultural citizenship--and constructing identities as language learners and productive workers."--